1990
DOI: 10.1073/pnas.87.12.4421
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional basis of the developmental regulation of human coagulation factor IX gene: factor IX Leyden.

Abstract: Hemophilia B Leyden is characterized by unusual developmental regulation of factor IX synthesis in affected individuals. One family affected with the hemophilia B Leyden phenotype was found to have a specific single-base mutation (G----A) at nucleotide -6 of the factor IX gene. The mutation site was found in a small region of the 5'-untranslated sequence designated the Leyden-specific region (LS region). This region, approximately 40 base pairs in length, contains the unique mutation sites of all the known fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
37
2

Year Published

1991
1991
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 25 publications
7
37
2
Order By: Relevance
“…All of those studies were performed in vitro, with the implicit assumption that the puberty-related male sex hormone surge is directly involved. In contrast, our earlier works in vitro did not support a direct role for either testosterone or androgen receptors (13,14). One transgenic mouse model study was previously reported for a hemophilia B Leyden mutation, A ϩ 13G (20).…”
contrasting
confidence: 39%
See 1 more Smart Citation
“…All of those studies were performed in vitro, with the implicit assumption that the puberty-related male sex hormone surge is directly involved. In contrast, our earlier works in vitro did not support a direct role for either testosterone or androgen receptors (13,14). One transgenic mouse model study was previously reported for a hemophilia B Leyden mutation, A ϩ 13G (20).…”
contrasting
confidence: 39%
“…1A, all of these mutations are clustered in an approximately 50 base pair (bp) region, nucleotide (nt) -34 through nt ϩ19 (see ref. 12 for nt numbering), known as the Leyden-specific region (LSR) in the 5Ј UTR (13,14). The wild-type gene LSR is known to bind 3 nuclear proteins, HNF-4 (15), an unidentified protein binding to the region spanning the nt -6 site (hereafter called UKP-6) (13) and C/EBP (16).…”
mentioning
confidence: 99%
“…It has been found that promoter mutations in factor IX (4,7,12,19,28,39,45,47,49), protein C (2), haptoglobin (16), and ␤-globin (10,31,(36)(37)(38) lead to disruption of the binding of transcription factors, with a resulting clinically significant reduction of gene expression. Such a lesion might be expected to affect the level of expression of the factor VIII protein and give rise to a clinical phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The amphotropic retroviruses of dLSNBAIX and dLSNBTIX were prepared by transfecting vector DNA into packaging cells, SCRIP (19), with the calcium phosphate precipitation method (20). The LIXSN retrovirus was prepared by transfecting vector DNA, LIXSN, into the ecotropic packaging cell line, (-2 (21) Proc.…”
Section: Kb) a Bamhi Fragment Containingmentioning
confidence: 99%
“…Clotting Activity of Factor IX. Factor IX activity was determined by the one-stage clotting assay employing human factor IX-deficient plasma (20). Normal human plasma pooled from 30 healthy individuals who showed normal blood clotting parameters was used as a standard for ELISA and the clotting assay.…”
Section: Kb) a Bamhi Fragment Containingmentioning
confidence: 99%